Fenugreek Anaphylaxis in a Pediatric Patient. (April 2018) - Joseph, Nancy I.; Slavin, Eileen; Peppers, Brian P.; Hostoffer, Robert W.
Fenugreek ( Trigonella foenum-graecum) is a food product that belongs to the Leguminosae family along with other legumes. It has been used in India, Greece, and Egypt for culinary and medical purposes since ancient times, and today, fenugreek is used for flavoring foods, dyes, and drugs throughout the world. Many members of the Leguminosae family have been associated with allergies including soybean, green pea, and peanut. Fenugreek is also included in this family and may result in allergic reactions. Two cases of anaphylaxis have been described in children after ingestion of curry and pastes that contain fenugreek, although the true nature of the causative agent was unclear. We report the first case of fenugreek anaphylaxis in a pediatric patient defined by skin testing, immunoglobulin E ImmunoCAP assays, and clear ingestion.